The Performance of POMSE Treatment using Different Synthesized Green Zinc Oxide-Cymbopogon Nardus (ZnO-CN) using Photocatalytic Reactor - Muhamad Najib, Alya Batrisyia; Zainuddin, Nurfarah Adila; Muhamad, Aida (Multidisciplinary Applied Research and Innovation, 2023)
Palm oil production is essential in Malaysia since it impacts to the economic growth. However, palm oil mill secondary effluent (POMSE) has a high color intensity that could be detrimental to aquatic life. Membrane photocatalytic reactor (MPR) have emerged as one of the most promising technologies for treating palm oil mill secondary effluent (POMSE). This study intended to treat POMSE with the presence of utilising several kinds of zinc oxide (ZnO) nanoparticles in MPR, including ZnO-cymbopogon nardus (ZnO-CN) at varying concentrations (1%, 4%, and 8%), ZnO commercial, and non-synthesized green ZnO. The sampling of the sample was carried out at 10 minutes interval for 3 hours. Then, the treated sample was tested in terms of their color using Hach DR 6000. It had been found that ZnO-CN8 yields the highest performance in the color reduction of POMSE (23.63%). Thus, it can be inferred that this study influences the efficacy of the MPR system in the treatment of POMSE with the presence of green photocatalysts.